Battle on two fronts: Fournier’s gangrene as a devastating complication of targeted radiotherapy for advanced adenocarcinoma rectum - Athiyaman, Adithyan; Surees Kumar, S; Norbert Victor, Vinslet Prissilla (Indian Journal of Case Reports, 2025)
Fournier’s gangrene (FG), as a complication of rectal carcinoma, is exceptionally rare and life-threatening. This case reports an unusual presentation of radiotherapy-induced FG in a 75-year-old male patient with advanced rectal adenocarcinoma. Multiple surgical debridements provided temporary stabilization, supported by targeted antibiotics and airway management. However, progressive polymicrobial sepsis necessitated a multidisciplinary approach, which was unsuccessful due to underlying poor prognostic factors. This case underscores the need for standardized clinical guidelines and management protocols to improve patient outcomes and reduce mortality in similar cases.